Synthesis and Evaluation of [N-methyl-11C]N-Desmethyl-loperamide as a New and Improved PET Radiotracer for Imaging P-gp Function - Lazarova, Neva; Zoghbi, Sami S; Hong, Jinsoo; Seneca, Nicholas; Tuan, Ed; Gladding, Robert L; Liow, Jeih-San; Taku, Andrew; Innis, Robert B; Pike, Victor W (Journal of medicinal chemistry, 2008)
[11C]Loperamide has been proposed for imaging P-glycoprotein (P-gp) function with positron emission tomography (PET), but its metabolism to [N-methyl-11C]N-desmethyl-loperamide ([11C]dLop; [11C]3) precludes quantification. We considered that [11C]3 might itself be a superior radiotracer for imaging brain P-gp function and therefore aimed to prepare [11C]3 and characterize its efficacy. An amide precursor (2) was synthesized and methylated with [11C]iodomethane to give [11C]3. After administration of [11C]3 to wild-type mice, brain radioactivity uptake was very low. In P-gp (mdr-1a(−/−)) knockout mice, brain uptake of radioactivity at 30 min increased about 3.5-fold by PET measures, and over 7-fold by ex vivo measures. In knockout mice, brain radioactivity was predominantly (90%) unchanged radiotracer. In monkey PET experiments, brain radioactivity uptake was also very low but after P-gp blockade increased more than 7-fold. [11C]3 is an effective new radiotracer for imaging brain P-gp function and, in favor of future successful quantification, appears free of extensive brain-penetrant radiometabolites.